ANALISIS PENERAPAN LANGKAH-LANGKAH PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK DALAM KURIKULUM 2013 PADA PEMBELAJARAN BIOLOGI DI SMA NEGERI SE-KOTA MEDAN - Jimmy Francius Simbolon; Jhonas Dongoran (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Scientific approach is one of approach applied in the Curriculum of 2013. The Scientific approach designed student as the subject of learning and teacher as a facilitator and motivator. In this design, teacher is not must explain all of the teaching material. There are 5 steps of the scientific approach which is abbreviated into 5M as follows: observing, asking, gathering information, reasoning, and communicating. The Objective of this study are (1) to measure the scientific approach application in the curriculum of 2013 in High Schools of Medan City, (2) to find out the obstacles commonly faced by Biology teachers in the application of scientific approach in the Curriculum of 2013 in State High Schools in Medan and (3 ) to find out the school facilities and infrastructure that supports the application of the scientific approach in the Curriculum of 2013 at State High Schools in Medan. This research was conducted in State High School in Medan City. The research held on July - September 2019. The research applied descriptive method to find out the application of scientific approach steps in State High School in Medan City. The instruments in this study were observation, questionnaire, and interview. The data were analyzed by the scientific approach data analysis and also by the analysis of observation data. This research is targeted to be publishes in any National non-Accredited Journal. The TKT proposed in this research is on a scale of 1 which shows the basic principles of learning technology with a recorded scientific approach